Relevance of TH2 Markers in the Assessment and Therapeutic Management of Severe Allergic Asthma: A Real-Life Perspective - Caminati, M; Vianello, A; Chieco Bianchi, F; Festi, G; Guarnieri, G; Marchi, M R; Micheletto, C; Olivieri, M; Tognella, S; Guerriero, M; Senna, G (Journal of investigational allergology & clinical immunology, 2020)
Although blood eosinophils are currently recognized as the main clinical marker of TH2-type inflammation, their relevance in identifying asthma severity remains a matter of debate. Our retrospective real-life study on severe asthmatics included in the NEONet Italian database aimed to investigate the relevance of blood eosinophil count and fractional exhaled nitric oxide (FeNO) in the clinical assessment of severe asthma and their role as potential predictors of responsiveness to anti-IgE therapy. The cut-off values chosen were 300 eosinophils/mm3 and FeNO of 30 ppm. We evaluated 132 adult patients. No significant differences were observed between the groups (high and low baseline eosinophil counts) in terms of demographic data, total IgE, lung function, patient-reported outcomes, or nasal comorbidities. The Asthma Control Test score and Asthma Quality of Life Questionnaire scores were poorer in patients with FeNO ≥30 ppb than in patients with FeNO <30 ppb. In the high FeNO subgroup, more frequent hospital admissions and a higher number of working days lost in the previous year were registered. A combined score including both eosinophils and FeNO did not improve the accuracy of the individual parameters. In the high-eosinophil subgroup, the proportion of responders to omalizumab was greater and increased at each follow-up time point. Our findings show that blood eosinophil count is not an unequivocal marker of asthma severity, whereas a higher FeNO level is associated with more frequent hospital admissions and more working days lost. Blood eosinophils seem to act as a predictor of response to omalizumab.